Street‐level bureaucrats, rule‐following and tenure: How assessment tools are used at the front line of the public sector. (17th January 2018) - Assadi, Anahita; Lundin, Martin
Abstract : Studies on street‐level bureaucracy examine actions of frontline workers within the public sector. In this literature, there is a lack of evidence on how job tenure affects how frontline workers respond to formal steering. We contribute to prior research by studying the nationwide introduction of an assessment support tool to be used by caseworkers to assess clients' needs under the Swedish active labour market policy. We examine the potential effects of tenure on how caseworkers use this tool. The empirical analysis is based on quantitative and qualitative data. We show that as tenure increases, street‐level bureaucrats, especially male caseworkers, tend to act in accordance with policy signals to a lesser extent. The qualitative analysis shows that this pattern can partly be explained by the fact that increasing experience with meeting clients face to face increases caseworkers' perceived confidence and skills.